“Diálogos, closes, atraques e babados : identidades delineadas na e pela linguagem sob uma perspectiva bakhtiniana” - Lopes, Thiago Rodrigues (2013)
In this research, under the theoretical focus of the Bakhtin Circle, we will search to realize the ways and processes of delineation of identity and personal brand of a group of people who identify themselves as Gay, Lesbian, Bisexual and Transgender, residents in Cuiaba-MT. Over time, studies about gender and sexualities sought natural and objective truths, in which both quantitative and qualitative studies ended up to identify, document, and describe sexual and gender identities. Such studies disregarded the objects from their contexts, building the idea of fixed and / or natural identities, and largely neglecting the linguistic processes involved in their formation. Thus, we point out that the language is a useful field to glimpse the processes of identity constitution and personal brands. We walked through a methodological approach, on the trail of qualitative action research, whose focus was on dialogic interactions and listed under the concrete utterence. Thereby, we offered the workshop intervention "Dialogues, close-ups, ruffles," which was held at the Institute of Languages – IL, Federal University of Mato Grosso, and relied on four volunteer people who identified themselves as gay (2 people), lesbian (1 person), transsexual (1 person). The workshop was recorded on audio and video, which facilitated the transcription of data. Concomitant with the data analysis happens the revision and construction of the remaining chapters of the research. This research is part of the research project "Rereading Bakhtin: the Bakhtin Circle contributions for a dialogical analysis of discourses produced in different spheres of human activity", developed by the research group Rereading Bakhtin (REBAK), from the Post-Graduating Program – MeEL of the Federal University of Mato Grosso.